Effect of soil texture, moisture regimes and cultivars on root and shoot development in upland rice (Oryza sativa) - SINGH, R K; SINGH, C V; SINHA, P K; SINGH, V P; MAITI, D; PRASAD, K (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted on root and shoot systems during 1994 and 1995 on 6 upland fice (Oryza sativa L.)cultivars (Japonica, Indica, Aus and Zero groups) grown in PVC pipes filled with sandy and sandy loam soils understressed (booting to harvest stage) and watered conditions. The component of root and shoot systems included, tillernumber, shoot dry weight, shoot height and diameter, adventitious root number, root diameter, rooting depth, rootweight, root mass distribution in soil layers. The result showed that the tiller number, shoot weight, shoot height andshoot diameter decreased due to stress but drought resistant Japonica cultivars had higher tiller number and droughtsusceptible Indica rices had higher shoot due to stress in sandy soil. The reduction in shoot weight due to stress inJaponica rice grown in sandy soil was less (5.3%), whereas the reduction was higher (10.1-24.2%) in Indica rice. Thetiller nuruber had direct relationship with adventitious root number and root number had inverse relationship withroot diameter. The magnitude of total root weight and root: shoot ratio differed within the rice cultivars and the rootweight and root: shoot ratio was higher due to stress in all cultivars. The Japonica rices gave higher root weight thanIndica, Aus and Zero group rices. The root diameters were affected due to stress as well as due to soil type. The rootdiameter decreased due to stress in sandy loam soil and increased in sandy soil. Under watered condition the rootconcentration was more in surface layer and under stress, the roots moved downwards in deeper layer.